Generative AI Governance Model in Educational Research - Pinho, Isabel; Costa, António Pedro; Pinho, Cláudia (Frontiers in Education, 2025)
This paper presents a scoping review on the application of generative artificial intelligence (GenAI) in educational research and proposes a living GenAI governance model to ensure a critical, responsible, and ethical usage of GenAI at macro, meso, and micro levels. Employing a quantitative and qualitative integration methodology, this review utilized two software tools: VOSviewer provided an initial overview of the field, while Bibliometrix revealed its conceptual structure. Through a two-dimensional map, subthemes were categorized into four quadrants: motor themes, basic themes, emerging or disappearing themes, and niche themes. Following the bibliometric analysis, we conducted a more detailed examination through content analysis by reviewing the titles and abstracts of 194 publications, selecting 35 pertinent articles. Based on these findings, we propose a Living GenAI Governance Model that maintains an ethical foundation and a dynamic perspective for using GenAI in educational research. The study’s limitations serve as starting points for future research, as this review utilized only one database (WoS). Future studies should expand on the use of databases and include updated references, given the rapid theoretical production and practical application in this field. The target audience for this article is diverse and spans multiple levels, including policymakers, academic authorities, university managers, students, teachers, and researchers. The primary contribution of this work lies in its comprehensive and structured vision of the model, which facilitates the study of inter-level relationships and the dynamic mapping of its various components.